The influence of brand image and word of mouth on purchase decisions at the 3 Second Fashion Store in Palangka Raya City - Syafe’i, Muhammad (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
This research investigates the impact of brand image and word of mouth on consumer purchasing decisions at Toko Fashion 3Second in Palangka Raya. With the rapid growth of the fashion industry and the influx of various distribution outlets (distros) in Indonesia, this study highlights the competitive dynamics and consumer behaviour in the local context. Brand image and word of mouth have been identified as significant factors influencing consumer choices and loyalty. These are crucial for distros like Toko Fashion 3Second to thrive in a saturated market. This thesis utilizes quantitative analysis methods, with data gathered from consumer surveys and sales records, to explore the relationship between these variables and purchasing decisions. The findings indicate that both brand image and word of mouth significantly affect consumer decisions, guiding distros in refining their marketing strategies to enhance customer satisfaction and brand loyalty. The implications of this study extend to the strategic management of brand reputation in the highly competitive fashion industry